PERANCANGAN DASHBOARD PERAMALAN UNTUK MEMBANTU PT XYZ DALAM PERENCANAAN BARANG JADI DENGAN ARIMA - Natasya
PT XYZ is a medium-sized UMKM operating in the retail fashion industry, established in 2015 in Bandung, West Java. PT XYZ began by selling bags, clothing, and travel-related accessories. In its efforts to stay competitive in the market, PT XYZ has implemented continuous improvement by integrating information systems into its business processes. However, the company has faced challenges with its warehouse preparing areas being consistently full. To address this issue, PT XYZ initially carried out material planning (forecasting) using qualitative forecasting techniques, relying on the production capacity of suppliers. This approach has led to several negative impacts, including financial issues, warehouse overload, and overstocking for the material itself.